2011
DOI: 10.1037/a0021969
|View full text |Cite
|
Sign up to set email alerts
|

An observation on the spontaneous noticing of prospective memory event-based cues.

Abstract: In event-based prospective memory, current theories make differing predictions as to whether intention-related material can be spontaneously noticed (i.e., noticed without relying on preparatory attentional processes). In 2 experiments, participants formed an intention that was contextually associated to the final phase of the experiment, and lures that overlapped to differing degrees with the features of the intention-related cues were embedded in the initial phase. When participants were outside of the appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
64
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 46 publications
7
64
1
Order By: Relevance
“…Our results support the conclusion that intention interference represents a cue-driven, spontaneous process (Cohen et al, 2005;Knight et al, 2011;Scullin et al, 2009) that occurs in the absence of monitoring. There was no incentive to monitor during the lexical decision task (Knight et al, 2011;Marsh et al, 2006), and all participants reported that they understood that the prospective memory task was finished following the image-rating block.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Our results support the conclusion that intention interference represents a cue-driven, spontaneous process (Cohen et al, 2005;Knight et al, 2011;Scullin et al, 2009) that occurs in the absence of monitoring. There was no incentive to monitor during the lexical decision task (Knight et al, 2011;Marsh et al, 2006), and all participants reported that they understood that the prospective memory task was finished following the image-rating block.…”
Section: Discussionsupporting
confidence: 88%
“…A characteristic of spontaneous retrieval is that it occurs without intention; thus, the occurrence of the word dancer was expected to produce (spontaneous) retrieval of intentionrelated information, which would be revealed by slowed lexical decision responding to the target (relative to control) words. This intention interference effect (Cohen et al, 2005), which has been observed reliably in younger adults Knight et al, 2011;Scullin et al, 2009), suggests that some aspect of the prospective memory intention was spontaneously noticed, detected, or retrieved when the target cue was processed.…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…Findings of increased response time to PM lures demonstrate that ongoing task items can receive extra individual attention if their stimulus properties partially or exactly match PM targets (Knight, Meeks, Marsh, Cook, Brewer & Hicks, 2011). PM goals are likely to be spontaneously retrieved when PM lures are processed, with the increased response time caused either by this initial noticing or by subsequent target verification, intention retrieval, or response coordination (Knight et al, 2011).…”
mentioning
confidence: 99%